The impact of fiscal decentralization on economic growth in Indonesia - Ari Mulianta Ginting; Muhammad Zilal Hamzah; Eleonora Sofilda (Universitas Islam Indonesia, 2019)
Fiscal decentralization was firstly implemented in 2001 and has brought a new era of local autonomy in Indonesia. The objective of fiscal decentralization to local government is to increase the economic growth and public service. This research uses a panel data regression and quadrant analysis method with the data of cluster districts and cities in Indonesia from 2013 to 2018. Findings/Originality: The panel regression estimation shows that fiscal decentralization has a positive and significant effect on economic growth in all clusters. However, the quadrant analysis results show that on average 86.7% of all clusters districts and cities were in quadrant IV which reflects low fiscal decentralization and low economic growth. The implication of the result is that the government should increases the allocation of capital expenditure in local budget to accelerate local economic growth of the districts/cities in all clusters.